Oribatula (Zygoribatula) exilis subsp. exilis exilis (Nicolet 1855 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Oribatula (Zygoribatula) exilis exilis (Nicolet, 1855) Material – Two specimens in Karadedeoğlu Village, Tekkeyaylası Area, Taşköprü forest, N 41° 22′ 24.45′′, E 34° 23′ 25.15′′, alt. = 1224 m, 2 August 2018, tree trunk of P.nigra; 8 specimens in Çiftlik Village, Tekçam Area, Taşköprü forest, 15 May 2018, N 41° 15′ 19.75′′, E34° 14′ 06.85′′, alt. = 1329 m, tree bark and debris of P. nigra . Previous record in Turkey – Ankara (Grobler et al. 2005). Global distribution – Holarctic. Ecology – All types of habitats.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 265, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Oribatula exilis; Arthropoda; Oribatulidae; Arachnida; Animalia; Oribatula (zygoribatula) exilis exilis (nicolet, 1855); Biodiversity; Sarcoptiformes; Oribatula; Taxonomy; 15. Life on land